Best Answer

The sum of the equation - 990 + 880 +90 +790 +690 + 50, is found as follows;

990 + 880 +90 +790 +690 + 50

= (990 + 880) + (90 +790) + (690 + 50)

= ( 1870 ) + (880 ) + ( 740 )

= 3490

Answer = 3490

Q: What is the sum of 990 plus 880 plus 50 plus 90 plus 790 plus 690 plus 50?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The sum of the equation - 990 + 880 +90 +790 +690 + 70, is found as follows;990 + 880 +90 +790 +690 + 70= (990 + 880) + (90 +790) + (690 + 70)= ( 1870 ) + (880 ) + ( 760 )= 3510Answer = 3510

The sum of the equation - 990 + 880+40 +90 +790 +690, is found as follows;990 + 880 +40 +90 +790 +690= (990 + 880) + (40 +90) + (790 + 690)= ( 1870 ) + ( 130 ) + ( 1480 )= 3480Answer = 3480

The answer = 3490

The answer = 3510

90 + 900 = 990

Related questions

The sum of the equation - 990 + 880 +90 +790 +690 + 20, is found as follows;990 + 880 +90 +790 +690 + 20= (990 + 880) + (90 +790) + (690 + 20)= ( 1870 ) + (880 ) + ( 710 )= 3460Answer = 3460

The sum of the equation - 990 + 880 +90 +790 +690 + 40, is found as follows;990 + 880 +90 +790 +690 + 40= (990 + 880) + (90 +790) + (690 + 40)= ( 1870 ) + (880 ) + ( 730 )= 3480Answer = 3480

The sum of the equation - 990 + 880 +90 +790 +690 + 60, is found as follows;990 + 880 +90 +790 +690 + 60= (990 + 880) + (90 +790) + (690 + 60)= ( 1870 ) + (880 ) + ( 750 )= 3500Answer = 3500

The sum of the equation - 990 + 880 +90 +790 +690 + 70, is found as follows;990 + 880 +90 +790 +690 + 70= (990 + 880) + (90 +790) + (690 + 70)= ( 1870 ) + (880 ) + ( 760 )= 3510Answer = 3510

The sum of the equation - 990 + 880+40 +90 +790 +690, is found as follows;990 + 880 +40 +90 +790 +690= (990 + 880) + (40 +90) + (790 + 690)= ( 1870 ) + ( 130 ) + ( 1480 )= 3480Answer = 3480

The answer = 3450

The answer = 3460

The answer = 3520

The answer = 3450

The answer = 3460

The answer = 3470

The answer = 3480